Common mode filter design for mitigation of bearing degradation in inverter-fed Motor drive systems - Fan, Fei (Nanyang Technological University, 2020)
Recent advancements in the insulated-gate bipolar transistor (IGBT) enable higher switching speeds in power electronics and have improved the power conversion efficiency significantly. Hence, pulse width modulated (PWM) variable frequency drives (VFDs) are widely used in modern control of electro-mechanical drive systems. On the other hand, higher switching frequencies cause the presence of high-frequency common-mode (CM) voltage, which results in unwanted CM current flows through the motor bearing and leads to premature motor bearing failures, such as frosting, fluting and pitting. Consequently, new drive installations can fail within months, which results in unplanned and costly system downtime. Thus, it is important to understand the different cause-and-effect chains of different types of bearing current so that cost-effective mitigation techniques for a certain drive configuration can be proposed. A prototype consists of a commercially available inverter and a 5.5 kW induction motor is used as a system-under-investigation to better understand the fundamental mechanism of bearing degradation and the necessary countermeasures. Modifying and hardening the bearing design may not be always possible and may affect the overall operation of the motor. Hence, it is best to have an effective solution without modifying the motor and adding an external CM filter to attenuate the CM current entering into the induction motor is explored in this thesis. Optimal CM filter design requires prior knowledge of both the source and termination impedances of the filter. To facilitate the measurement of the source and termination impedances, an inductive coupling approach is adopted to extract these impedances. To allow the proposed inductive coupling approach be used in high-power motor drive systems, further improvements are necessary to extract in-circuit CM impedance of a motor drive system. Such improvements offer enhanced signal-to-noise ratio under a harsh electrical background noise environment. With the successful extraction of in-circuit source and termination impedances, a suitable CM filter can be designed systematically to achieve the desired attenuation without guessing and overdesigning. In the evaluation of first-order single-inductor and second-order LC filters, it is found that the second-order filter may not be always a better choice due to DM-to-CM conversion in the motor drive system, as the system is usually asymmetrical in nature. With the known information of the CM noise source and termination impedances, one can also evaluate the effect of the mode conversion on the CM filter design in a quantitative way.